THE INFLUENCE OF LEADERSHIP STYLE ON FINANCIAL PERFORMANCE WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE - Akibun, Fitria; Lestari, Bekti Wiji; Meilandri, Detti; Kaluku, Moh Ramdhan Arif; Ridhayanto, Muhammad (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research is a quantitative study with an explanatory approach, namely an approach that relies on any previous research as the main reference, namely research to produce new innovations, namely the addition of the Good Corporate Governance variable in this study. The data used in this article is a type of primary data obtained through direct interviews with employees in the financial sector of Bank Rakyat Indonesia throughout Indonesia which contains 10 question items from three types of themes using a multiple-choice method containing statements strongly agree, agree, normal/so-so, disagree, and strongly disagree. The data used in this article is analyzed using the smart PLS 4.0 analysis tool with the hypothesis below. Keywords: Leadership Style,Financial Performance , Good Corporate Governance